ACADEMIC SUPERVISION AND TEACHERS’ PEDAGOGICAL COMPETENCE: A QUALITATIVE STUDY OF PRINCIPAL PRACTICE IN AN ELEMENTARY SCHOOL - Sigit Setiyo Budi; Eni Sulistyarini; Anggun Fauziana K; Soedjono (SOSIOEDUKASI, 2026)
This study aims to examine the implementation of academic supervision conducted by the principal in improving teachers’ pedagogical competence at SD Negeri Jombor, Jumo District. A qualitative descriptive approach was employed to explore the planning, implementation, follow-up, and impact of academic supervision on teachers’ pedagogical practices. Data were collected through in-depth interviews, classroom observations, and document analysis involving the principal and teachers. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that academic supervision has been implemented through structured planning and classroom observation; however, it has not been carried out optimally due to limited time, uneven supervision frequency, and the absence of systematic follow-up programs. Academic supervision contributes positively to improving teachers’ pedagogical competence, particularly in lesson planning and instructional implementation, although improvements in student-centered learning and assessment practices remain limited. The study highlights the importance of needs-based, collaborative, and continuous academic supervision to enhance teachers’ pedagogical competence effectively.